Ozone Exposure and Asthma Attack in Children - Huang, Wanting; Wu, Jinzhun; Lin, Xiaoliang (Frontiers in Pediatrics, 2022)
Background: Increasing evidence indicates that air pollution can trigger asthma attacks in children. Purpose: This study aimed to explore the association between ambient ozone (O3) and asthma exacerbation in children, and to provide scientific evidence for the health effects of ozone in the future. Methods: We collected the data of asthma attacks in children from the First Affiliated Hospital of Xiamen University, air pollution data, and meteorological data in Xiamen during 2016-2019. A case-crossover design and conditional logistic regression models were applied for data analyses, conducted to evaluate the association between asthma attacks and outdoor air pollution with lag structures (from lag 0 to lag 6) in both single and multi-pollutant models. Furthermore, we estimate the influence of various levels of ozone exposure on an asthma attack, divided into three groups by O3-8h (O3-8h ≥ 100 μg/m3, O3-8h: 80-99 μg/m3, O3-8h < 80 μg/m3). Results: In the single-pollutant model, it is found that the effect of ozone in the three days before the asthma attack is the largest (OR: 1.0035, 95% CI: 1.0007-1.0063). Every 10 μg/m3 increase of PM2.5, PM10, NO2, SO2, and CO in lag 2 were positively associated with asthma attack, with odds ratios of 1.0078 (95% CI: 1.0033-1.0125), 1.0075 (95% CI: 1.0045-1.0105), 1.6842 (95% CI: 1.1177-2.5380), and 1.0297 (95% CI: 1.0149-1.0448), respectively. When ozone concentration was higher than 80 μg/m3, it was positively associated with acute asthma attacks from lag 0 to lag 6. The positive effect of O3 was significant when ozone concentration was higher than 100 μg/m3. Conclusion: Relatively low ozone (O3-8h > 80 μg/m3) will increase the risk of asthma attacks in children.